A subjetivação capitalística como mecanismo de precarização do trabalho docente na educação superior brasileira - Bechi, Diego (2019)
The main objective of this doctoral thesis is to explain how the subjectivity of higher education teaching workers is constituted in the current process of hegemonic expansion of toyotist / neoliberal rationality and how the model of capitalist subjectivation has interfered with working conditions and modes. / life projects of these higher education professionals in Brazil. This is an exploratory study, regarding the objectives, and bibliographical, of a hermeneutic-analytical nature, regarding the procedures. By means of this eminently qualitative investigative procedure, the following problem is explored: to what extent the capture of subjectivity by neoliberal rationality, whose requirement of universalization of the competition norm provided the construction of a new subject (subject-company / company) self-governing), has contributed to the process of intensifying and precarious teaching work in higher education institutions? The theoretical framework on the process of capitalist subjectivation, developed by leading researchers linked to the areas of sociology, philosophy and education - such as P. Dardot, C. Laval, F. Guattari, G. Alves and D. Mancebo - enables a new reading key to understand the mechanisms of intensification and precariousness of teaching work. The thesis defended in this research comprises the following assertion: the formation of subjectivity (productivist and competitive) has become one of the main mechanisms used by the flexible accumulation model to increase the efficiency and productivity of teaching workers, as well as to subject them to poor working conditions. The neoliberal economicism and the privatism and the metamorphoses in the world of work towards the flexible mode of production, inherent to the new cycle of universalization of capitalism, led the direction of educational policies in favor of the mercantilist interests and the (subjective) formation of a new education professional, more productive, competitive and flexible to the demands of the market. Among the consequences of this process of subjectivation, the destruction of labor rights and the subsumption of education professionals to the dictates of the productivist / mercantilist logic and the culture of performativity stand out.